2011
DOI: 10.1111/j.1095-8649.2011.02919.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological stimuli change expression of genes and neutrophil function in fathead minnow Pimephales promelas Rafinesque

Abstract: Fathead minnows Pimephales promelas were exposed to lipopolysaccharide (LPS) and polyinosinic-polycytidylic acid [poly(I:C)] to observe immunological responses during simulated bacterial and viral challenge at the level of gene expression and granulocyte function. Complementary DNA libraries were created from LPS- and poly(I:C)-treated fish and c. 5000 expressed sequence tags (ESTs) were sequenced. The ESTs were subjected to BLASTx analysis and 1500 genes were annotated, grouped by function and 20 immune genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Neutrophil defence mechanism involves the release of respiratory burst as well as neutrophil extracellular traps (NET) release to kill pathogens. Neutrophils rely on NADPH oxidase system to ferry electrons across cell membranes into phagocytic vacuoles during respiratory burst to create ROS which stimulates the release of the digestive enzymes responsible for microbial deaths (Jovanovic, Goetz, Goetz, & Palić, ). In the present study, TCMBS application showed increased neutrophil induced immune defence readiness through a significant increase in the production of ROS in splenic neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil defence mechanism involves the release of respiratory burst as well as neutrophil extracellular traps (NET) release to kill pathogens. Neutrophils rely on NADPH oxidase system to ferry electrons across cell membranes into phagocytic vacuoles during respiratory burst to create ROS which stimulates the release of the digestive enzymes responsible for microbial deaths (Jovanovic, Goetz, Goetz, & Palić, ). In the present study, TCMBS application showed increased neutrophil induced immune defence readiness through a significant increase in the production of ROS in splenic neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals were challenged with an intra-peritoneal injection of LPS (Sigma; St. Louis, USA; L4005; 10μg/g fish at 1g/L [44]) or SRBC (Sigma R3378; 20μg/g fish at 1g/L [42, 45]) for experimental treatments, and 0.01mL of saline solution (PBS) for controls. Prior to injection, all fish were lightly anesthetized in a clove oil solution, and after injection animals were placed immediately in aged tap-water where they recovered within 1–2 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the relative proportion of thrombocytes, lymphocytes and monocytes varied significantly following 15 days after Phdp exposure, compared to control fish exposed to PBS. In contrast, no significant differences were found in thrombocyte, lymphocyte and monocyte counts, 24 and 48 h after injecting fathead minnow, Pimephales promelas (Rafinesque), with different pathogen‐associated molecular patterns such as lipopolysaccharides and polyinosinic‐polycytidylic acid (Jovanovic, Goetz, Goetz & Palić ). A reduction in the number of blood lymphocytes has been reported in fish after bacterial insults (Lamas, Santos, Bruno, Toranzo & Anadón ; Balfry, Shariff & Iwama ; Garcia et al .…”
Section: Discussionmentioning
confidence: 97%